The Tacit Dimensions of Normative Rules - R.T. Allen (Rosenberg & Sellier, 2020)
All rules are normative. Using Polanyi’s tacit integration, this article shows that all rules have tacit dimensions in their creation by recognition of regularities, application and modification, all of which cannot be made wholly explicit. J. Searle holds that some regular actions are not the following of unconscious rules, but ignores the fact that they have been tacitly formed by recognising of regularities. Tacitly known and practised rules are transmitted by apprentices observing the actions and judgements of masters, and then across generations by tradition. Thus knowledge and belief cannot be neither clearly distinguished nor separated. Justificatory, critical and foundational philosophies are to be replaced by a fiduciary and fallible one.